2019
DOI: 10.1177/1475240919889823
|View full text |Cite
|
Sign up to set email alerts
|

Students’ (Inter)National Identities within International Schools: a Qualitative Study

Abstract: Debates surrounding national and international identity are becoming increasingly prevalent with the rise of nationalist and populist rhetoric in the public sphere. International schools, which are growing in number, serve as valuable sites for conducting research on national and international identity as they can be viewed as a representation of the increasing diversification of many schools around the world. The aim of the study described in this article is to determine how the national and international ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
1
1
0
1
Order By: Relevance
“…This connects with Fitzsimons’ study which found that students often had what they termed an ‘(inter)national identity’, recognizing that some individuals may affiliate with more than one national identity, or not connect with one at all (2019: 276). Anastasia felt connected not only with her international school, but also with the term ‘third culture kid’ and the idea of students from other international schools with similar backgrounds.…”
Section: Resultssupporting
confidence: 72%
“…This connects with Fitzsimons’ study which found that students often had what they termed an ‘(inter)national identity’, recognizing that some individuals may affiliate with more than one national identity, or not connect with one at all (2019: 276). Anastasia felt connected not only with her international school, but also with the term ‘third culture kid’ and the idea of students from other international schools with similar backgrounds.…”
Section: Resultssupporting
confidence: 72%
“…In terms of curriculum, many international schools offer a standardised curriculum such as the International Baccalaureate. Critics assert that there is an intellectual colonisation of Anglo-Western themes within international curricula, with students studying the history of Western countries and not their countries of origin (Fitzsimons, 2019). This Anglo-Saxon orientation within the teaching demographic and the curriculum against the backdrop of a diverse student body likely increases the prevalence of name-based microaggressions among ethnic minorities.…”
Section: Racial Context In Singapore Schoolsmentioning
confidence: 99%
“…La EI puede ser interpretada por los colegios desde las perspectivas globalista e internacionalista que perfila la identidad pedagógica en sus propuestas educativas junto con las historias de vida, expectativas y preconcepciones que trae consigo el alumnado al aula (Allan, 2015). Esta convergencia de valores crea un espacio único para el desarrollo de la identidad del alumnado (Fitzsimons, 2019) el cual, pone de manifiesto el sentido de la EI implementado en las escuelas. Lo anterior puede ser ejemplificado con el hecho de que un colegio internacional puede plantear una propuesta educativa basada en la EI desde una perspectiva internacionalista, pero sin llegar a cumplir dicho cometido; mientras que la EI puede ser experimentada por el alumnado que estudia en una escuela que no especifica su carácter internacional (Hayden & Thompson, 2013) poniendo en evidencia la proliferación de colegios que se catalogan como internacionales que da lugar a una narrativa cínica y poniendo en duda la legitimidad de centro educativo (Bunnell, 2019).…”
Section: El Centro Educativo Como Fomento De La Ei En Uno O Varios En...unclassified